Perbandingan Pola Manajemen Keuangan pada Tiga Masjid Besar di Yogyakarta (Studi Kasus pada Masjid Jogokariyan, Muttaqien, dan Gedhe Kauman) - Izza Maulida Santoso; Muhammad Akhyar Adnan (UIR Press, 2018)
This study is trying to compare the financial management of the three biggest and most welknown Masjid in Yogyakarta: Masjid Jogokariyan, Masjid Muttaqien, and Masjd Gedhe Kauman. The selection are based on three main variables which include the volume of cash flow, number of jamaah, and the financial management practices based on the following criteria: the organizational sructure and separation of function, personnel selection management, formulation of strategies in financial management, financial statements, and evaluation. The study applies the exploratory method. The simple descriptive analysis are conducted on data collected and triangulation data collected from three different viewpoints. Based on the data analysis, the study found that there are different financial management practices. The three biggest Masjid have simple financial statements. In addition, one of the Masjid has not applied the criteria of personnel selection. Generally the three biggest Masjids have applied the practice of financial management, although their implementation in doing so is very simple. The practice needs to be improved. Morever the three biggest Masjid have not yet applied the ideal Financial Management, as well as financial statements in accordance with applicable standards.